Detecção e intervenção precoce na educação infantil de Presidente Prudente: DIPEIPP - Guerrero, Katiane Mayara [UNESP]; van den Broek, Vanessa Niens [UNESP]; Alves, Aline Sayuri Tacaki [UNESP]; Defende, Ana Paula Guirro [UNESP]; Gonzaga, Caroline Nunes [UNESP]; Messias, Yasmin Coladello [UNESP]; André, Larissa Borba [UNESP]; Oliveira, Mileide Cristina Stoco de [UNESP]; Pereira, Andressa Sampaio [UNESP]; Frasson, Isabela Bortolim [UNESP]; Olah, Sabrina Lopes [UNESP]; Andrino, Amanda dos Santos [UNESP]; et al. (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Delays in psychomotor development are often associated with loss of biological, psychological and social order, therefore, early detection of problems in development has been shown to be important so that there is or to prevent problems in the long run. Objective: To evaluate the motor profile of children enrolled in early childhood education directed by the municipal education of Presidente Prudente - SP. Methodology: This is a quantitative and qualitative research, a case study with descriptive. Sample comprised 29 children of both sexes, with 12 girls and 17 boys, aged 4.5 years. As a research tool, we use the Motor Development Scale - EDM. Results: Of the 29 children evaluated, one was rated on their performance motor for scale much higher, on average 5 normal 5 Normal low, 4 in lower and 13 in much lower. Conclusion: Most of the children showed gaps in their motor development after evaluation with the EDM. From the evaluation, it was possible to identify those changes in motor development, identified early, forwarding them so for specialized services.

Introdução: Atrasos no desenvolvimento neuropsicomotor estão frequentemente associados a prejuízos de ordem biológica, psicológica e social, por esse motivo, a detecção precoce de problemas no desenvolvimento tem se mostrado importante para que não haja ou que previnam problemas em longo prazo. Objetivo: Avaliar o perfil motor das crianças matriculadas na educação infantil encaminhadas pela secretaria municipal da educação de Presidente Prudente – SP. Metodologia: Trata-se de uma pesquisa quanti-qualitativa, do tipo estudo de caso com natureza descritiva. Amostragem foi composta por 29 crianças de ambos os sexos, sendo 12 meninas e 17 meninos, com idade entre 4,5 anos. Como instrumento de pesquisa, utilizamos A Escala De Desenvolvimento Motor – EDM. Resultados: das 29 crianças avaliadas, 1 foi classificada em seu desempenho motor pela escala em muito superior, 5 em normal médio, 5 em normal baixo, 4 em inferior e 13 em muito inferior. Conclusão: A maior parte das crianças avaliadas apresentou lacunas em seu desenvolvimento motor após avaliação com a EDM. A partir da avaliação, foi possível à identificação dessas alterações no desenvolvimento motor, sendo identificadas precocemente, encaminhando-as assim, para serviços especializados.
Keywords: EDM; Early intervention; EDM; Intervenção precoce